Cervical left pulmonary artery. Issue 1 (23rd January 2018) - Schmidt, Matthew Q; Hafertepe, Michael; Fortuna, Randall; Abdullah, Ibrahim; Richardson, Randy
Abstract: We detail what we believe to be the first reported case of a congenital 'Cervical Left Pulmonary Artery' in which an aberrant left pulmonary artery courses cranially into the mid-cervical neck before descending back into the thorax to the left pulmonary hilum. Due to the location and course of the artery, we believe that this anomaly is likely due to a developmental error of the sixth pharyngeal arch. Ultimately, the use of a reconstructed 3D computed tomography image provided detailed characterization of the unique anatomical variant, aiding in a successful surgical repair of the defect.